NGOs Mediating Peace Promoting Inclusion in Myanmar's Nationwide Ceasefire Negotiations - Palmiano Federer, Julia (Twenty-first Century Perspectives on War, Peace, and Human Conflict,, 2024)
Can informal actors such as NGOs mediate peace agreements? If so, how does it work and what are the consequences for international peace mediation? This book tackles these questions and more through looking at the role of nongovernmental (NGO) mediators in promoting "inclusive peace" to negotiating parties in Myanmar's Nationwide Ceasefire Agreement (NCA) negotiations from 2011-2015. The author argues that NGO mediators, traditionally seen as part of civil society or as weak mediators with little power or leverage, have become established mediation actors alongside more formal actors and are redefining the mediation field through norm promotion. However, even if NGO mediators can promote norms, the book questions whether they should promote norms in the first place, as the NCA process shows how the promotion of inclusivity contributed to a more exclusive outcome of years of peace negotiations in Myanmar. The outcome of the NCA process presents a critical andcautionary tale of promoting a presumed universal norm into a given locale and expecting a certain outcome without understanding how an external norm interacts with existing normative frameworks. This is an open access book. Julia Palmiano Federer holds a PhD in Political Science from the University of Basel and a Master in International Affairs from The Graduate Institute of International and Development Studies in Geneva, Switzerland. Dr. Palmiano Federer is a Postdoctoral Fellow at the University of Ottawa and the Head of Research at the Ottawa Dialogue, an organisation that specializes in the resolution of armed conflicts around the world through Track Two diplomacy, a form of unofficial and informal dialogue between warring parties. She is also currently a Senior Fellow at the Negotiation and Conflict Resolution Collaboratory at the Harvard Kennedy School's Center for Public Leadership.